A Mediating Model To Evaluates Employee Performance In Retail Amid And Post COVID 19 - Jefri Van Novis; Yulihasri; Donard Games (Institute of Computer Science (IOCS), 2022)
Employee performance has become increasingly important in the literature, attracting the attention of many scholars in the last decade. This study adopted an employee-centered perspective to guide its examination of the relationship among spiritual leadership and job satisfaction to individual performance, then an investigation of the mediation of employees’ affective commitment. An analysis was conducted of data collected from 208 employees working in a retail store with thirteen of branch’s. The results reveal statistically significant and positive effects of spiritual leadership on employee performance and affective commitment. Then, job satisfaction statistically not significant effect on employee performance but affective commitment. Affective commitment has presented strong contribution as mediating variable, and strong direct impact to employee performance.